TRAF1 Gene Polymorphism Correlates with the Titre of Gp210 Antibody in Patients with Primary Biliary Cirrhosis - Agnieszka Kempinska-Podhorodecka; Zakera Shums; Michał Wasilewicz; Ewa Wunsch; Malgorzata Milkiewicz; Dimitrios P. Bogdanos; Gary L. Norman; Piotr Milkiewicz (Clinical and Developmental Immunology)
Background. Polymorphisms of TRAF1 (Tumor necrosis factor receptor-associated factor 1) are associated with rheumatoid arthritis (RA). Whether TRAF1 polymorphisms confer increased risk for primary biliary cirrhosis (PBC), an autoimmune liver disease which can co-exist with RA, is unknown. Aim of the Study. To assess the frequency of the RA-conferring susceptibility TRAF1 polymorphisms rs3761847 and rs2900180 in a cohort of PBC patients. The association of TRAF1 polymorphisms with clinical features and autoantibody markers was also analyzed. Methods. We studied 179 PBC patients and 300 controls. Samples were genotyped for TRAF1 gene polymorphisms by real-time PCR. Autoantibodies were tested by ELISA. Results. The frequency of rs3761847 and rs2900180 polymorphisms did not differ between patients and controls. Laboratory or clinical features were not associated with specific polymorphisms. Gp210 autoantibody titres were conspicuously higher among GG homozygotes of rs3761847 as compared with AA homozygotes (P=0.02). In contrast, antichromatin titers were higher in AA compared to GG rs3761847 homozygotes (P=0.04). Rheumatoid factor IgG titres were significantly higher in rs2900180 TT homozygotes than CC homozygotes (P=0.02). Conclusions. TRAF1 polymorphisms occur with the similar frequency in PBC patients and in the general population, but their presence is probably involved in the regulation of specific PBC-related autoantibodies.